Janeway's immunobiology. - Janeway, Charles Alderson, Jr., 1943-2003; Murphy, Kenneth, ....-; Travers, Paul, 1956-; Walport, Mark Jeremy, Sir, 1953- (New York : Garland, 2008)
Janeway's Immunobiology, Seventh Edition is an introductory text for use in immunology courses for undergraduates, graduate students, and medical students. It guides the reader through the immune system in all its aspects-from the first engagement of innate immunity to the generation of the adaptive immune response and its clinical consequences. The Seventh Edition has been comprehensively updated throughout, and includes new information on topics such as NK cells, Toll-like receptors, AID, viral evasins, mucosal immunity, and celiac disease, to name a few. Each copy of the book includes a revised CD-ROM, Immunobiology Interactive, which contains animations and videos with voiceover narration, as well as the figures from the text in PowerPoint® and JPEG formats for presentation purposes. New discussion questions have been provided at the end of Chapters 2-16. These questions can be used for review, or as the basis for discussion in class or in informal study groups. As in previous editions, a caduceus icon in margins indicates topics which are correlated to Case Studies in Immunology, Fifth Edition <http://www.garlandscience.com/textbooks/0815341451.asp > by Geha and Rosen. Janeway's Immunobiology continues to set the standard for currency and authority with its clear writing style and organization, full-color art program, scientific accuracy, and consistent viewpoint-that of the host's interaction with an environment containing many species of potentially harmful microorganisms.